This I Believe - Weiman, Elton Ewart "Tad" (Tufts Archival Research Center, 2006)
E. E. Wieman explains the importance of sharing in life and how sharing is exemplified in sports; however, Wieman also describes how learned to share from his mother, which is the basis of his optimism.